New cetacean fossils from the late Cenozoic of South Africa - Govender, Romala; Marx, Felix G. (Frontiers in Earth Science, 2023)
Marine sediments from the western coast of southern Africa record the origin of the Benguela Upwelling System, one of the most productive in the world. High productivity, in turn, is reflected in a diverse marine mammal fossil assemblage, comprising whales, dolphins and a phocid seal. Here, we describe new records of baleen whale (mysticete) fossils from the early Pliocene localities of Saldanha Steel, Milnerton and Langebaanweg, as well as several potentially younger specimens trawled from offshore sediments. The presence of the extinct rorquals Diunatans and Fragilicetus suggests biogeographical links with the eastern North Atlantic and, thus, potentially antitropical population structuring. The trawled specimens also include rorquals (e. g. the blue whale, Balaenoptera cf. musculus), as well as a right whale (Eubalaena) and a pygmy right whale (Caperea). The latter is the first fossil of this family every discovered in Africa, and only the seventh specimen to be reported worldwide.